Guard Cell-Specific Pectin METHYLESTERASE53 Is Required for Abscisic Acid-Mediated Stomatal Function and Heat Response in Arabidopsis - Wu, Hui-Chen; Yu, Shih-Yu; Wang, Yin-Da; Jinn, Tsung-Luo (Frontiers in Plant Science, 2022)
Pectin is a major component of the plant cell wall, forming a network that contributes to cell wall integrity and flexibility. Pectin methylesterase (PME) catalyzes the removal of methylester groups from the homogalacturonan backbone, the most abundant pectic polymer, and contributes to intercellular adhesion during plant development and different environmental stimuli stress. In this study, we identified and characterized an Arabidopsis type-II PME, PME53, which encodes a cell wall deposited protein and may be involved in the stomatal lineage pathway and stomatal functions. We demonstrated that PME53 is expressed explicitly in guard cells as an abscisic acid (ABA)-regulated gene required for stomatal movement and thermotolerance. The expression of PME53 is significantly affected by the stomatal differentiation factors SCRM and MUTE. The null mutation in PME53 results in a significant increase in stomatal number and susceptibility to ABA-induced stomatal closure. During heat stress, the pme53 mutant highly altered the activity of PME and significantly lowered the expression level of the calmodulin AtCaM3, indicating that PME53 may be involved in Ca2+-pectate reconstitution to render plant thermotolerance. Here, we present evidence that the PME53-mediated de-methylesterification status of pectin is directed towards stomatal development, movement, and regulation of the flexibility of the guard cell wall required for the heat response.